A Sternoclavicular Joint-Specific Plate for the Displaced Medial-End Clavicle Fracture - Zhu, Yunli; Liu, Fucun; Lin, Lie; Zhang, Chuanyi; Wang, Bin; Wang, Shouli (Frontiers in Surgery, 2022)
Background: Surgical techniques for displaced medial-end clavicle fractures with small medial fragments are still challenging. This study aimed to introduce a sternoclavicular joint (SCJ)-specific plate and evaluate the clinical and radiological results of medial-end clavicle fracture treated with this plate. Methods: From January 2006 to December 2020, 31 patients with displaced medial-end clavicle fractures were included in this study, with 8 patients with accompanying SCJ dislocation. Abduction and forward elevation of the shoulder, the Visual Analogue Scale (VAS), and the American Shoulder and Elbow Surgeons Score (ASES) were used for evaluation before index surgery and at the latest follow-up. Results: After an average of 98.5 (range, 13 to 171) months, the mean VAS significantly decreased from 6.8±1.0 preoperatively to 0.9±0.8 at the latest follow-up (P<0.001). The mean ASES score significantly increased from 34.3±7.8preoperatively to 90.2±4.9 at the latest follow-up (P<0.001). The mean abduction of the shoulder significantly increased from 72.1±6.6 preoperatively to 169.5±8.5 at the latest follow-up (P<0.001). The mean forward elevation of the shoulder significantly increased from 97.1±11.0 preoperatively to 163.1±11.5 at the latest follow-up (P<0.001). The union of all fractures was achieved, and all implants were removed. No loose or breakage of implants was observed. No vascular or nerve damage occurred during the operation. Conclusions: This SCJ-specific plate provided excellent long-term results for the treatment of displaced medial-end clavicle fractures and was an alternative implant for medial-end clavicle fractures with or without small or comminuted medial fragments, especially those associated with SCJ dislocation.